Artificial Intelligence in Entrepreneurship Education: A Nine-Year Bibliometric Analysis and Future Research Directions Toward the Sustainable Development Goals - Choiru Umatin; Vina Budiarti Mustika Sari; Nailariza Umami; Komm Pechinthorn; Eni Susilowati (UNIVERSITAS NEGERI SURABAYA, 2026)
Objective: This research aims to map research trends in Artificial Intelligence in Entrepreneurship Education which are linked to achieving the SDGs. Method: This research uses a bibliometric approach from the Scopus database which focuses on related themes in the 2017-2025 period. Biblioshiny as a tool and data analyzed descriptively. Results: Research trends on Artificial Intelligence in Entrepreneurship Education show a very significant increase and are appropriate for achieving SDGs, especially points four and eight. The most contributing countries are China and Indonesia. An interesting theme to research is the integration of AI in adversarial machine learning, federated learning, contrastive learning, educational computing in entrepreneurship. Future research direction refers to the design of advanced AI-based entrepreneurship education as well as innovations in various robust AI models for business. Policy recommendations should be in line with increasing the capacity of AI pedagogy teachers and assisting AI training for entrepreneurship. Novelty: This research offers AI research trends in entrepreneurship education according to the framework of achieving the SDGs with the latest data.